THE CHARACTERISTICS OF THE AGROFORESTRY SYSTEMS IN LOCAL COMMUNITIES NEAR LORE LINDU NATIONAL PARK - Golar, Golar (Journal of Agroecology, 2015)
Local communities in many places have experienced in land use decisions, especially on Agroforestry systems. We examine the communities near Lore Lindu National Park (LLNP), who practicing the Agroforestry systems. This paper presents the typology of Agroforestry of the community near LLNP in Central Sulawesi. This research used qualitative-descriptive analysis by employing Geographic Information System (GIS), and The New Environmental Paradigm (NEP) analysis. The result shows that are two dominant agroforestry typologies in the research area: home garden and mixed garden. It is found that the mixed garden is dominant (combining many trees with cocoa, coffee, fruits, ect. According to the NEP analysis, it is also found that individual attitudes in Salua villagers are more dominant than in Simoro counterparts. The orientation in Salua is dominated by economic value. In contrast, Simoro has an altruistic value, that is, the land use system is not only for the economic orientation, but also for the socio-cultural value.